The Integration of Pancasila Values ​​in Sexual Education (SIPELAS) as an Effort to Prevent Sexual Violence Against Children: Integrasi Nilai-Nilai Pancasila Dalam Pendidikan Seksual (SIPELAS) Sebagai Upaya Pencegahan Kekerasan Seksual Pada Anak - Syafiq Rizqullah, Muhammad; Zhafran Ramadhan, Muhammad; Aprilia, Eka; Goang Swaradesy, Rufus; Maria Azzahra, Illiyyina (Citizenship Education, Faculty of Education, Jambi University, 2025)
This research employs a descriptive qualitative approach that aims to comprehensively and thoroughly describe the phenomenon of sexual violence against children. This research employed digital observation through SIMFONI-PPA (Online Information System for Women and Child Protection) data, which presents real-time information regarding cases of violence against women and children in Indonesia, both verified and unverified cases. Data analysis was conducted by positioning the researcher as the main instrument interpreting events and social situations related to the phenomenon of sexual violence against children. The research findings indicate that the SIPELAS Program (Sila Pendidikan Pelecehan Seksual/Pancasila Principles Sexual Harassment Education) can serve as a strategic solution for preventing sexual violence through the integration of Pancasila values in sexual education. This program is implemented through three systematic stages: teacher training for sexual education, parent training, and material delivery to students with learning media adapted to educational levels ranging from animation for kindergarten level to discussions and webinars for senior high school level. Each principle in Pancasila has relevance in preventing sexual violence, where the values of divinity, humanity, unity, democracy, and social justice can serve as moral foundations in shaping children's character to respect themselves, others, and uphold human dignity.